Reaction rates in a theory of mechanochemical pathways. Issue 27 (24th August 2016) - Quapp, Wolfgang; Bofill, Josep Maria
Abstract : If one applies mechanical stress to a molecule in a defined direction then one generates a new, effective potential energy surface (PES). Changes for minima and saddle points (SP) by the stress are described by Newton trajectories on the original PES (Quapp and Bofill, Theor. Chem. Acc. 2016, 135, 113). The barrier of a reaction fully breaks down for the maximal value of the norm of the gradient of the PES along a pulling Newton trajectory. This point is named barrier breakdown point (BBP). Depending on the pulling direction, different reaction pathways can be enforced. If the exit SP of the chosen pulling direction is not the lowest SP of the reactant valley, on the original PES, then the SPs must change their role anywhere: in this case the curve of the log(rate) over the pulling force of a forward reaction can show a deviation from the normal concave curvature. We discuss simple, two‐dimensional examples for this model to understand more deeply the mechanochemistry of molecular systems under a mechanical stress. © 2016 Wiley Periodicals, Inc. Abstract : Assume a pulling along the direction of the Newton trajectory from minimum R to minimum P. Shown is an overlay of the stationary points of diverse effective surfaces under the pulling. Used are 16 equidistant loads. The point is the final BBP of the direction. An upper saddle moves downward, but a lower saddle moves uphill: so, the common rate of a forward reaction can become abnormal. Level lines of the original PES are shown as background where around the minimums dense lines are used.